Le grain contre le bétail : la contestation d’un ordre socio-politique imposé - Emmanuelle Veuillet (Revue Internationale des Études du Développement)
This article shows that the outbreak and persistence of conflicts between displaced herders and the local inhabitants of Mundri results from the transformation of the political system operated by the governing military authorities (the SPLM/A) during the second civil war (1983-2005). These cattle-related conflicts are neither a mechanical reaction to the arrival of displaced herders from other regions, nor the outcome of heightened competition over local resources, but are rather related to the identity of Dinka herders and their specific relation with the SPLM/A, which has enabled them to benefit from a very privileged position within the new political order.